Parametric characteristics of a solar thermophotovoltaic system at the maximum efficiency. (15th October 2016) - Liao, Tianjun; Chen, Xiaohang; Yang, Zhimin; Lin, Bihong; Chen, Jincan
Graphical abstract: A model of the far-field TPVC driven by solar energy, which consists of an optical concentrator, an absorber, an emitter, and a PV cell and is simply referred as to the far-field STPVS. Highlights: A model of the far-field solar thermophotovoltaic system (STPVS) is established. External and internal irreversible losses are considered. The maximum efficiency of the STPVS is calculated. Optimal values of key parameters at the maximum efficiency are determined. Effects of the concentrator factor on the performance of the system are discussed. Abstract: A model of the solar thermophotovoltaic system (STPVS) consisting of an optical concentrator, a thermal absorber, an emitter, and a photovoltaic (PV) cell is proposed, where the far-field thermal emission between the emitter and the PV cell, the radiation losses from the absorber and emitter to the environment, the reflected loss from the absorber, and the finite-rate heat exchange between the PV cell and the environment are taken into account. Analytical expressions for the power output of and overall efficiency of the STPVS are derived. By solving thermal equilibrium equations, the operating temperatures of the emitter and PV cell are determined and the maximum efficiency of the system is calculated numerically for given values of the output voltage of the PV cell and the ratio of the front surface area of the absorber to that of the emitter. For different bandgaps, the maximum efficiencies of the system are calculated and the corresponding optimum values of several operating parameters are obtained. The effects of the concentrator factor on the optimum performance of the system are also discussed.